Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/eurheartj/ehab674
|View full text |Cite
|
Sign up to set email alerts
|

Defining cardiovascular toxicities of cancer therapies: an International Cardio-Oncology Society (IC-OS) consensus statement

Abstract: The discipline of Cardio-Oncology has seen tremendous growth over the past decade. It is devoted to the cardiovascular (CV) care of the cancer patient, especially to the mitigation and management of CV complications or toxicities of cancer therapies, which can have profound implications on prognosis. To that effect, many studies have assessed CV toxicities in patients undergoing various types of cancer therapies; however, direct comparisons have proven difficult due to lack of uniformity in CV toxicity endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
194
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(253 citation statements)
references
References 143 publications
2
194
0
3
Order By: Relevance
“…These definitions are in keeping with a recent consensus statement from the International Cardio-Oncology Society. 70 The safety of BRAF inhibitor and MEK inhibitor use in patients with a baseline LVEF that is either below 50% or the institutional lower limit of normal has not been established and therefore these drugs should be used with caution for this patient group. 63 , 64 , 65 , 66 , 67 , 68…”
Section: Cardiovascular Toxicity Of Braf and Mek Inhibitors In Patien...mentioning
confidence: 99%
“…These definitions are in keeping with a recent consensus statement from the International Cardio-Oncology Society. 70 The safety of BRAF inhibitor and MEK inhibitor use in patients with a baseline LVEF that is either below 50% or the institutional lower limit of normal has not been established and therefore these drugs should be used with caution for this patient group. 63 , 64 , 65 , 66 , 67 , 68…”
Section: Cardiovascular Toxicity Of Braf and Mek Inhibitors In Patien...mentioning
confidence: 99%
“…However, since Lap is an oral drug, its administration was not checked by pharmacists, which might have led to the lower measurement rate. Prior reports 7) have pointed out that without baseline LVEF, accurate assessment of cardiotoxicity is not possible, so measurement of LVEF before the starting therapy is essential. Although previous studies have reported a low incidence of cardiotoxicity with Lap 1) , cardiotoxicity as a late adverse event of drug therapy can be a prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the context of immunotherapy-related cardiotoxicity, ERNA may be particularly beneficial for pretreatment assessment and to monitor cardiac function during therapy (including post-therapeutic surveillance). An application scenario can be patients with borderline LVEF in echocardiography, in whom accurate diagnosis influences further therapy management [ 1 , 156 ]. Moreover, the high repeatability might facilitate systemic evaluations in multi-centric clinical trials.…”
Section: Assessment Of Ventricular Function and Chamber Morphologymentioning
confidence: 99%
“…The emerging use of novel immunotherapies in cancer treatment increases the risk of immunotherapy-related cardiovascular side effects. Cardiotoxic damage ranges from asymptomatic changes to fulminant short- and long-term complications, including cardiomyopathies, arrythmias, and vascular disease [ 1 , 2 , 3 , 4 , 5 ]. In contrast to conventional chemotherapy, the use of targeted immunotherapies has expanded the forms and presentations of cardiovascular toxicity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation